Recipe for disaster? the deployment of patents over environmentally sound technologies (ESTs) - Ida Madieha, Abdul Ghani Azmi; Suzi Fadhilah , Ismail; Chun-Phuoc, Jeong (International Islamic University Malaysia, 2014)
The development, deployment and dissemination of low- carbon and other environmentally sound technologies (ESTs) is critical in our response to climate change. Yet, many of these critical technologies are patented and belong to private entities. Malaysia through the National Renewable Energy Policy and National Green Technology Policy, aims to leverage on green technology as a double edge sword; as a tool to spur economic activities whilst at the same time ensuring sustainable development and conservation of the environment for future generations. In order to enhance the uptake of ESTs, Malaysia has identified renewable energy as an impetus. This paper explores the discourse between the patents and climate change at the international level. As the diffusion of ESTs requires modification and adaptation, the issue of how much this can take place without the consent of the patent owner is discussed. The scope of scientific research exemption in Malaysia is examined with a view of determining whether it can support research activities with commercial activities and the act of inventing around a patent. It is proposed that for effective transfer of ESTs to take place, the scientific research provision be expanded to cover all forms of research necessary for the diffusion of technology, regardless of its commercial and transformative ends.